Real estate investment trust (reits) analysis: the Malaysian case - Mohamed, Suhana; Sham, Rohana; Jambari, Abdul Razak (2012)
The terms REITs refer to Real Estate Investment Trust which is a trust fund that invests in rental properties. REITs are investment vehicles which enable the flow of funds from investors to the real estate sector of the economy. It major income is coming from rental income and most of the profits must be distributed as dividend to its holders. The purpose of conducting this research was to reveals the information on factors that contributed to the development of REITs in Malaysia. The development is important and serve as reliable information to the investors in order to give knowledge and valuable information on the direction of REITs market in the future. The information should be highlighted to the public to give clearer picture to the investors on the trends the REITs market are heading for. The potential investors love this type of information beforehand. This research will also provide evidence on the performance of 14 REITs funds in Malaysia from 2001 to 2010. The data used for this research is secondary data which had been gathered from DataStream and Thomson One Banker website. The analysis on the performance used the traditional Finance method from Capital Asset Pricing Model (CAPM) which is Sharpe Index will give better insight for future investor before they start their investment. The analysis conducted to investigate which REITs perform better using historical prices and KLCI. The correlation analysis was also conducted to know the correlation between KLCI and REITs fund prices. The outcome of this research will be; the knowledge on future direction of REITs market and which REITs is the market leader.